THE EFFECT OF APTIN ON MYOCARDITIS IN PATIENTS WITH JUVENILE RHEUMATOID ARTHRITIS - Kabulova Mukhabbat Rustamovna (Western European Studies, 2025)
Juvenile rheumatoid arthritis (JRA) is a chronic autoimmune disease that is often accompanied by extraosseous manifestations, including cardiovascular disease. Myocarditis is one of the serious complications that aggravate the course of the disease. Aptin, as a protein involved in the regulation of the actin cytoskeleton, has potential significance in the pathogenesis of inflammatory processes and tissue remodeling. Studying its role in the development of myocarditis in JRA may contribute to the development of new therapeutic strategies
Keywords: inflammatory; strategies; development; potential